The Business Analysis of Green Catfish (Mystus nemurus) Enlargement on Fish Pond In Sungai Paku Village, Sub-District of Kampar Kiri, District of Kampar, Riau Province - Sari Yulianti; Eni Yulinda; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research about the business analysis of green catfish (Mystus nemurus) enlargement on fish pond was conducted on January, 2016 in Sungai Paku Village, Sub-District of Kampar Kiri, District of Kampar, Riau Province. This study aims to (1) determine the input-output business enlargement of fish pond of green catfish, (2) analyzed the business enlargement of fish pond of green catfish and (3) the feasibility business of enlargement of fish pond of green catfish. The method used is a survey method that includes observation, interviews and documentation.Based on the results of research (1) stocking density in each pond with an area of 200-500 m2 as much as 3000-7500 fish / pond / crop with total production of 468-1065 kg / pond / crop, (2) the average production costs incurred in enlargement business of green catfish with an area of 200-500 m2 of Rp 11,767,400, - / harvest up to Rp 27,171,500, - / harvest with total receipts received by Rp 15.912 million, - / harvest up to Rp 36.21 million, - / harvest and great benefits received Rp 4.1446 million,-/ harvest up to Rp 9.0385 million, - / harvest and (3) enlargement business of fish pond of green catfish in Sungai Paku feasible with RCR value> 1, the FRR values> 6.02% and the value of PPC is between 3.44 to 3.63 per period or ± 1 year and 3 months. Keywords : Enlargement Baung, The Business Analysis, Sungai Paku village